Feminist Solutions for Ending War - MacKenzie, Megan; Wegner, Nicole (Pluto Press, 2021)
'War is a man's game,' or so goes the saying. Whether this is true or not, patriarchal capitalism is certainly one of the driving forces behind war in the modern era. So can we end war with feminism? This book argues that this is possible, and is in fact already happening. Each chapter provides a solution to war using innovative examples of how feminist and queer theory and practice inform pacifist treaties, movements and methods, from the international to the domestic spheres. The contributors propose a range of solutions that include arms abolition, centring Indigenous knowledge, economic restructuring, and transforming how we 'count' civilian deaths. Ending war requires challenging complex structures, but the solutions found in this edition have risen to this challenge. By thinking beyond the violence of the capitalist patriarchy, this book makes the powerful case that the possibility of life without war is real.